Video Consultations and Their Utilization by Orthopedic and Trauma Surgeons During the COVID-19 Pandemic. A Go-To Technology in the Future or Just a Stopgap? - Daentzer, Dorothea (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background During the COVID-19 pandemic, the contact restrictions imposed for protection against infection have limited the options for direct medical therapy. Considering this, the present study aimed to evaluate the utility of the rarely used online video consultation as an alternative treatment form for orthopedic and trauma surgeons and analyze its potential for future use.Methods During calendar week 24 in the year 2020, 215 specialists in orthopedics and orthopedics and trauma surgery in the city and greater region of Hanover, Germany, were enrolled in a questionnaire-based evaluation of their use of video consultations. The analysis consisted of 125 completed questionnaires, which corresponded to a return rate of 58.1%. The completed questionnaires recorded the number of users, frequency of utilization, and advantages and disadvantages of online treatment, as well as provided an assessment of the future use of telemedicine and video consultations. Furthermore, we considered the necessary requirements for using video consultations and for continuing their use in the future as well as the potential of performing online consultations given that all pertinent conditions are fulfilled.Results Among the 125 respondents, only 17 (13.6%) had already experienced video consultations, all starting during the COVID-19 pandemic, but with very low frequencies (maximum of one–three times per week). Despite the limitations, the advantages included helping patients receive the required treatments and reducing the need for travel. However, the respondents mentioned that there were several disadvantages due to diagnostic limitations: there was no direct examination, primary consultations were restricted, and possibilities of consultations and explanations were reduced. Of the 108 (86.4%) respondents who had not experienced video consultations, only 9 (8.3%) had specifically planned to conduct online consultation, whereas 57 (52.8%) had no such intention in the foreseeable future and 42 (38.9%) were undecided on this point. They stated diagnostic limitations because of the lack of direct examination (44/77.2%) and the indispensable personal contact with the patient (30/52.6%) as main counter-arguments. According to all the respondents, the main requirements for the implementation of video consultations included establishment of proper technology (81.6%), adequate remuneration (61.6%), legal certainty (58.4%), fast and unbureaucratic support for installation and in case of problems (51.2%), and a manageable bureaucracy during the initial period (44.8%).Conclusion Video consultations and telemedicine in general undoubtedly have advantages, primarily concerning the protection from infection and contact restrictions, which are increasingly requested by patients. However, the collected data indicate that this approach may remain less important than personal consultations in the field of orthopedics and trauma surgery. As suggested by available data, this does not apply to other fields such as psychotherapy or general medicine.
Keywords: COVID-19 pandemic; online consultation; orthopedics; telemedicine; video consultation